Hard tube pulser for 150 MW klystron - Bak, P.A.; Goncharov, A.D.; Kazarezov, I.V.; Leonov, V.V.; Skarbo, B.A.; Cherniakin, A.D.; Bieler, M. (Вопросы атомной науки и техники, 1999)
The development of adequate modulators for high peak power klystrons is one of the focus points for linear collider R&D programs. For the DESY/THD Sband linear collider study 150MW RF pulse power at 50Hz repetition rate and 3mks pulse duration is required. Two different modulator schemes were investigated. One is the conventional line type pulser, using a pulse forming network and a step up transformer, the other one is a Hard Tube Pulser, using a DC power source at the full klystron voltage and a switch tube. The main advantages of a Hard Tube Pulser are short rise and fall times of the HV pulse, resulting in high efficiency and simpler design.